Performance of cardio-pulmonary resuscitation among medical students in a military medical faculty / Hasliza Abu Hassan, Aida Jaffar and Victor Feizal - Abu Hassan, Hasliza; Jaffar, Aida; Feizal, Victor (Universiti Teknologi MARA, 2023)
Cardiac arrest is an escalating public health problem as it contributes to cardiovascular morbidity and mortality, accounting for almost 15–20% of all deaths. Cardiac arrest may also occur among active individuals, such as during sports activities. Hence, Cardiopulmonary Resuscitation (CPR) is crucial and proven to prevent cardiac death when correctly performed. Precise CPR techniques do improve a patient’s prognosis and reduces complications. This study aimed to determine CPR knowledge among medical students in our medical faculty. This was a cross-sectional study involving 106 students in year 1, 2 and 5, with a response rate of 76.8%. A structured questionnaire was distributed among the students and included socio-demographic data collection and questions on CPR knowledge based on the CPR teaching module. More than half the students were male (58.5%) with a mean age of 21.6 (±1.71) years. The students' ethnicity comprised Malay (62.3%), Indian (26.4%) and Chinese (11.3%). The student subject proportions were 32.1% from year 1, 34.9% from year 2 and 33.0% from year 5. A majority were cadet students (71.7%). The preferred study method was self-study followed by study group. More than quarter of them used YouTube videos to improve their understanding, and only 5.7% used e-learning. As for CPR knowledge, 89.9% of the students passed the CPR assessment. Female students (p=0.04) and Year 5 students (p=0.006) were significantly associated with good CPR performance. Medical students be updated current CPR knowledge as CPR techniques evolve. The faculty needs to be proactive in delivering effective teaching methods and tools to improve CPR knowledge among our medical students to prepare them for future job practice.